Sensitive skin is a neuropathic disorder. Issue 12 (31st July 2019) - Huet, Flavien; Misery, Laurent
Abstract: Sensitive skin is defined by the occurrence of unpleasant sensations such as tingling, burning, tautness, itching or pain. Mechanisms explaining sensitive skin are controversial, and many hypotheses have been proposed. Because sensitive skin is primarily characterized by a wide variety of neuropathic‐like symptoms, it is highly likely that neurosensory dysfunction in the skin represents one of the pathological mechanisms of sensitive skin. This hypothesis does not exclude other explanations like role of keratinocyte, transient receptor potential channels, vasculature or environmental factors. Nevertheless, the role of the nervous system in the development of sensitive skin is crucial, and growing evidence supports this hypothesis. Pain and pruritus described by patients with sensitive skin correspond to neuropathic component, and its assessment shows an increase in neuropathic measures (DN‐4, Douleur Neuropathique 4) compared with control. These sensations are similar to the sensations observed in small‐fibre neuropathy (SFN), which is a group of disorders that affect thin nerve fibres. One study on the pathophysiology of sensitive skin demonstrated that intra‐epidermal nerve fibre density, especially of peptidergic C‐fibres, was lower in the sensitive skin group. A recent study showed a modification in heat‐pain detection threshold in patients with sensitive skin. All these results indicate that C‐fibre damage can help explain sensitive skin. Consequently, the role of the nervous system is increasingly obvious. Nevertheless, keratinocytes and other epidermal cells closely participate in sensory transduction. Therefore, the results of neurophysiological studies should be interpreted in the light of this information that the whole epidermis represents a huge polymodal nociceptor.